TYPES OF LANGUAGE INTERFERENCE IN DEVELOPING LEARNERS’ SPEAKING COMPETENCE IN ENGLISH, CAUSES AND CONSEQUENCES - Khudoyorova Gulasal Ilhomiddinovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In this article main types of linguistic interference, their reasons and effects  to  the  speech  of  students  are  learned.  During  the  research  phonological, grammatical,  lexical,  morphological,  pragmatic,  semantic,  idiomatic,  stilistic  and orthographic interferences are observed. The main goal of this article is to find most common  interferences  in  students,  learning  their  reasons  and  offering  effective solutions. In a research survey, interview, observation and online test methods were used. The results indicate that most students are facing challenges in phonetic and grammatical interference, and it depends on the differences between English and native languages. According to the overall results, it is recommended to conduct lessons using technologies, communicative approaches and comparative analysis. This article serves to eliminate and deeply understand linguistic interference and clarify practical ways for it.